Boron-doped coal tar pitch-based composite carbon aerogel and its preparation method and application
Through the preparation method of boron-doped coal asphalt-based carbon aerogel, the problems of graphitizing graphitization of sodium ion battery negative electrode materials are solved, and the specific capacity of the battery and the improvement of electrochemical performance are achieved. It is suitable for the negative electrode materials of sodium ion batteries.
Patent Information
- Application Number
- CN202410887135.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-07-03
AI Technical Summary
In the prior art, graphite, the negative electrode material of sodium ion batteries, cannot be directly applied due to the thermodynamic instability with sodium ions, and coal asphalt is easily graphitized during high-temperature carbonization, which is not conducive to sodium ion storage.
Through the preparation method of boron-doped coal asphalt-based carbon aerogel, coal asphalt and other raw materials are used to modify coal asphalt by chemical molecular cross-linking to form a coal asphalt/PVA/boronic acid hydrogel network, inhibit the formation of graphitized structures and increase the specific capacity of the battery.
It improves the specific capacity of the battery and improves the electrochemical performance of the electrode material. It is suitable for the negative electrode material of sodium ion batteries, and has the advantages of cheap raw materials, simple process and low cost.
Smart Images

Figure CN118651843B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a boron-doped coal tar pitch-based composite carbon aerogel and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the rapid development of society and the continuous innovation of technology, energy demand has also grown rapidly. However, the fossil fuel resources on the earth are limited. In recent years, wind energy, solar energy, tidal energy and other renewable and environmentally friendly energy have received widespread attention, but the direct output of these renewable and environmentally friendly energy sources is unstable or discontinuous. Therefore, how to establish a fixed and efficient energy storage system to meet the needs of daily life has become a major problem to be solved in the field of sustainable energy development.
[0004] Due to the thermodynamic instability of the compounds formed between sodium ions and graphite, graphite, the negative electrode material of commercial lithium-ion batteries, cannot be directly applied to sodium-ion batteries. It is crucial to find a suitable negative electrode material for sodium storage. Among them, coal tar pitch is a high-quality precursor for synthesizing sodium negative electrode materials due to its disordered microcrystals, high residual carbon rate, wide source of raw materials and low cost. However, coal tar pitch is easy to graphitize during the process of direct high-temperature carbonization without treatment, which is not conducive to the storage of sodium ions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing boron-doped coal tar pitch-based carbon aerogel; the present invention increases the functional groups of the prepared electrode material through boron doping, improves the defects on the surface of the electrode material, and effectively improves the specific capacity of the prepared battery; the preparation method has the advantages of cheap and readily available raw materials, simple process and low cost, etc.
[0006] The second object of the present invention is to provide boron-doped coal tar pitch-based carbon aerogel prepared by the above method.
[0007] The third object of the present invention is to provide an application of the above-mentioned boron-doped coal tar pitch-based carbon aerogel; the boron-doped coal tar pitch-based carbon aerogel has good electrochemical properties and can be used to prepare sodium ion batteries.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing boron-doped coal tar pitch-based carbon aerogel, the preparation method comprising the following steps:
[0010] (1) PVA is dissolved in deionized water, the pH value is adjusted with an alkaline solution, coal tar is added, the mixture is mixed evenly, and then an aqueous boric acid solution is added while stirring to obtain a coal tar-based hydrogel; the pH value is adjusted to ensure the formation of borate ester bonds; the alcoholysis degree of the PVA is (98-99) mole%, and the viscosity is (54-66) mpa.s
[0011] (2) The coal tar pitch-based hydrogel obtained in step (1) is freeze-dried and then carbonized at high temperature to obtain the boron-doped coal tar pitch-based carbon aerogel.
[0012] Furthermore, in step (1), the mass concentration of the PVA in deionized water is 1-10%.
[0013] Preferably, the mass concentration of the PVA in deionized water is 5-10%.
[0014] Furthermore, in step (1), the alkaline solution is a NaOH solution or a KOH solution, etc., and the concentration is (0.1-5) mol / L.
[0015] Preferably, the concentration of the alkaline solution is 0.5 mol / L.
[0016] Furthermore, in step (1), the pH value is 8-10.
[0017] Preferably, the pH value is 8.
[0018] Furthermore, in step (1), the coal tar pitch is sourced from lignite, bituminous coal or anthracite.
[0019] Furthermore, in step (1), the mass ratio of the coal tar pitch to PVA is 1:(0.1-10).
[0020] Preferably, the mass ratio of the coal tar pitch to PVA is 1:(0.5-10).
[0021] Furthermore, in step (1), the concentration of the boric acid aqueous solution is (1-5) mol / L.
[0022] Preferably, the concentration of the boric acid aqueous solution is 1 mol / L.
[0023] Furthermore, in step (2), the protective gas is nitrogen or argon.
[0024] Furthermore, in step (2), the high temperature carbonization temperature is (500-1500)°C and the time is (60-120) min.
[0025] Preferably, the high temperature carbonization temperature is (1200-1300)°C and the time is 60 min.
[0026] Furthermore, in step (2), after the high-temperature carbonization, the carbon aerogel is impregnated with dilute hydrochloric acid, and then filtered and dried to obtain the boron-doped coal tar pitch-based carbon aerogel.
[0027] Furthermore, the concentration of the dilute hydrochloric acid is (1-4) mol / L, which serves to remove the byproduct of NaOH.
[0028] Preferably, the concentration of the dilute hydrochloric acid is 3 mol / L.
[0029] The present invention adopts a chemical molecular cross-linking method to achieve the modification of coal tar pitch. In the cross-linking reaction, the medium and small molecules in the coal tar pitch are polymerized into high molecular weight substances, which can effectively improve the softening point and residual carbon rate of the coal tar pitch, and improve and regulate the microstructure of the carbonized product of the coal tar pitch. The present invention uses coal tar pitch as a carbon source, boric acid as a cross-linking agent and a boron source, and PVA as a modifier. The active groups in the polymer are used to react with the coal tar pitch molecules during high temperature annealing to form a copolymer, thereby forming a coal tar pitch / PVA / boric acid hydrogel network, wherein the network is mainly composed of the PVA chain cis-diol sites and borate ester bonds.
[0030] , regulate the microstructure of coal tar pitch, inhibit the formation of graphitized structure of coal tar pitch during high-temperature carbonization, and at the same time increase the active sites by boron doping through boric acid to enhance its application in sodium ion batteries.
[0031] The boron-doped coal tar pitch-based carbon aerogel prepared by the above method.
[0032] The application of the above-mentioned boron-doped coal tar pitch-based carbon aerogel, the boron-doped coal tar pitch-based carbon aerogel can be used to prepare a sodium ion battery, and the negative electrode material of the sodium ion battery includes the above-mentioned boron-doped coal tar pitch-based carbon aerogel.
[0033] Furthermore, the preparation method of the negative electrode material adopts the following steps:
[0034] ①, the boron-doped coal tar pitch-based carbon aerogel, the conductive agent and the binder are uniformly mixed, and then a solvent is added and mixed to obtain a slurry;
[0035] ②. The slurry obtained in step ① is evenly coated on a metal foil and vacuum dried to obtain the negative electrode material.
[0036] Furthermore, in step ①, the mass ratio of the boron-doped coal tar pitch-based carbon aerogel, the conductive agent and the binder is (7-8): (0.5-1.5): (0.5-1.5).
[0037] Preferably, the mass ratio of the boron-doped coal tar pitch-based carbon aerogel, the conductive agent and the binder is 8:1:1.
[0038] Furthermore, the conductive agent is carbon black, conductive graphite, carbon tube, graphene, Ketjen black, acetylene black or Super P, etc.
[0039] Furthermore, the conductive agent is acetylene black.
[0040] Furthermore, the binder is polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex (SBR) or carboxymethyl cellulose (CMC) and the like.
[0041] Furthermore, the binder is PVDF.
[0042] Furthermore, the solvent is 1-methyl-2-pyrrolidone solution or water.
[0043] Furthermore, the solvent is 1-methyl-2-pyrrolidone solution.
[0044] Furthermore, in step ②, the vacuum drying temperature is (50-60)°C and the time is (6-24) h; the metal foil is copper foil or aluminum foil. In this step, the solvent in the slurry is removed by vacuum drying, thereby forming an electrode sheet containing boron-doped coal pitch-based carbon aerogel on the surface of the copper foil.
[0045] Furthermore, the vacuum drying temperature is 60° C. and the time is 6 h.
[0046] Furthermore, the sodium ion battery also includes a separator, a positive electrode and an electrolyte.
[0047] Furthermore, the separator is glass fiber or polypropylene microporous membrane.
[0048] Furthermore, the diaphragm is glass fiber.
[0049] Furthermore, the positive electrode material is sodium metal.
[0050] Furthermore, the electrolyte is sodium hexafluorophosphate (NaPF6) solution or sodium perchlorate solution.
[0051] Preferably, the electrolyte is a sodium hexafluorophosphate solution.
[0052] Furthermore, the voltage window interval of the sodium ion battery is (0.01–3) V.
[0053] Beneficial effects: The present invention increases the functional groups of the prepared electrode material through boron doping, improves the defects on the surface of the electrode material, and effectively improves the specific capacity of the prepared battery; the preparation method of the boron-doped coal tar pitch-based carbon aerogel has the advantages of cheap and readily available raw materials, simple process and low cost, and meets the requirements of industrial production; the boron-doped coal tar pitch-based carbon aerogel has good electrochemical properties, can be used to prepare sodium ion batteries, and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute an improper limitation of the present invention.
[0055] Figure 1 Flow chart of preparing boron-doped coal tar pitch-based carbon aerogel in Example 1;
[0056] Figure 2 This is a SEM image of the boron-doped coal tar pitch-based carbon aerogel prepared in Example 1;
[0057] Figure 3 The charge and discharge curves of the materials prepared in Example 1 and Comparative Example 1. Specific embodiments
[0059] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0060] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the present invention are for demonstration purposes only. The present invention is further described according to the accompanying drawings and specific embodiments of the specification.
[0061] Example 1
[0062] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0063] (1) Preparation of coal tar-based hydrogel: PVA with a mass concentration of 5% was dissolved in deionized water at 90°C, and the pH value was adjusted to 8 with a NaOH solution with a solution concentration of 0.5 mol / L to ensure the formation of borate ester bonds; coal tar was then added and mixed evenly, with the mass ratio of coal tar to PVA being 1:0.1; finally, a boric acid aqueous solution with a concentration of 1 mol / L was added while stirring, and the mixture was mixed to obtain a coal tar-based hydrogel for later use. The coal tar used was derived from anthracite.
[0064] (2) Preparation of boron-doped coal tar pitch-based carbon aerogel: The coal tar pitch-based hydrogel obtained in step (1) was freeze-dried to obtain a xerogel, which was carbonized at a high temperature of 1200°C under argon protective gas and kept warm for 60 min. After being impregnated with 3 mol / L dilute hydrochloric acid, the xerogel was filtered and dried to obtain a boron-doped coal tar pitch-based composite carbon hydrogel.
[0065] 2. Preparation of sodium ion batteries:
[0066] (1) Grind the boron-doped coal tar-based carbon aerogel prepared in step 1, acetylene black and binder PVDF in a mortar at a mass ratio of 8:1:1, then add 1-methyl-2-pyrrolidone solution until the powder is a black viscous slurry for later use;
[0067] (2) Use a 100 μm scraper to evenly coat the slurry on a copper foil, then dry the copper foil at 60° C. for 6 h, and finally punch it into a circular electrode sheet with a diameter of 12 mm, which is the negative electrode;
[0068] (3) The electrode sheet obtained in step (2) is used as the negative electrode, sodium metal is used as the positive electrode, glass fiber is used as the separator, 1 mol / L NaPF6 solution is used as the electrolyte, and the voltage range is (0.01-3) V to prepare a sodium ion battery.
[0069] Example 2
[0070] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0071] (1) Preparation of coal tar-based hydrogel: PVA with a mass concentration of 7% was dissolved in deionized water at 90°C, and the pH value was adjusted to 8 using a 0.5 mol / L NaOH solution to ensure the formation of borate ester bonds; coal tar was then added and mixed evenly, with the mass ratio of coal tar to PVA being 1:0.1; finally, a 1 mol / L boric acid aqueous solution was added while stirring, and the coal tar was mixed to obtain a coal tar-based hydrogel for later use. The coal tar used was derived from anthracite.
[0072] (2) Preparation of boron-doped coal tar pitch-based carbon aerogel: The coal tar pitch-based hydrogel obtained in step (1) was freeze-dried to obtain a xerogel, and the obtained xerogel was carbonized at a high temperature of 1200°C under argon protective gas and kept warm for 60 min under this condition. After being impregnated with 3 mol / L dilute hydrochloric acid, it was filtered and dried to obtain the boron-doped coal tar pitch-based carbon aerogel.
[0073] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0074] Example 3
[0075] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0076] (1) Preparation of coal tar-based hydrogel: PVA with a mass concentration of 10% was dissolved in deionized water at 90°C, and the pH value was adjusted to 8 using a NaOH solution with a solution concentration of 0.5 mol / L to ensure the formation of borate ester bonds; coal tar was then added and mixed evenly, with the mass ratio of coal tar to PVA being 1:0.1; finally, a boric acid aqueous solution with a concentration of 1 mol / L was added while stirring, and the coal tar-based hydrogel was obtained by mixing and set aside. The coal tar used was anthracite.
[0077] (2) Preparation of boron-doped coal tar pitch-based carbon aerogel: The coal tar pitch hydrogel obtained in step (1) was freeze-dried to obtain a xerogel, which was carbonized at a high temperature of 1200°C under argon protective gas and kept warm for 60 min. After being impregnated with 3 mol / L dilute hydrochloric acid, the xerogel was filtered and dried to obtain a boron-doped coal tar pitch-based carbon aerogel.
[0078] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0079] Example 4
[0080] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0081] (1) Same as step (1) in step 1 of embodiment 1;
[0082] (2) Preparation of boron-doped coal tar pitch-based carbon aerogel: The coal tar pitch-based hydrogel obtained in step (1) was freeze-dried to obtain a xerogel, and the obtained xerogel was carbonized at a high temperature of 1300°C under a protective gas and kept warm for 60 min. After being impregnated with 3 mol / L dilute hydrochloric acid, the xerogel was filtered and dried to obtain a boron-doped coal tar pitch-based carbon aerogel.
[0083] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0084] Example 5
[0085] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0086] (1) Preparation of coal tar-based hydrogel: PVA with a mass concentration of 5% was dissolved in deionized water at 90°C, and the pH value was adjusted to 8 using a NaOH solution with a solution concentration of 0.5 mol / L to ensure the formation of borate ester bonds; coal tar was then added and mixed evenly, with the mass ratio of coal tar to PVA being 0.5; finally, a boric acid aqueous solution with a concentration of 1 mol / L was added while stirring, and the coal tar-based hydrogel was obtained by mixing and set aside. The coal tar used was derived from anthracite.
[0087] (2) Same as step (2) in step 1 of Example 1.
[0088] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0089] Example 6
[0090] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0091] (1) Preparation of coal tar pitch-based hydrogel: After dissolving PVA with a mass concentration of 5% in deionized water at 90°C, adjust the pH value to 8 using a NaOH solution with a solution concentration of 0.5 mol / L to ensure the formation of borate ester bonds; then add coal tar pitch and PVA in a mass ratio of 1 and mix evenly; finally, add a boric acid aqueous solution with a concentration of 1 mol / L while stirring, and mix to obtain a coal tar pitch-based hydrogel for later use. The coal tar pitch used is derived from anthracite.
[0092] (2) Same as step (1) in step 1 of Example 1.
[0093] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0094] Example 7
[0095] 1. Preparation of boron-doped coal tar pitch-based carbon aerogel:
[0096] (1) Preparation of coal tar-based hydrogel: PVA with a mass concentration of 5% was dissolved in deionized water at 90°C, and the pH value was adjusted to 8 using a 0.5 mol / L NaOH solution to ensure the formation of borate ester bonds; coal tar was then added and mixed evenly, with the mass ratio of coal tar to PVA being 2; finally, a 1 mol / L boric acid aqueous solution was added while stirring, and the coal tar was mixed to obtain a coal tar-based hydrogel for later use. The coal tar used was derived from anthracite.
[0097] (2) Same as step (1) in step 1 of Example 1.
[0098] 2. Preparation of sodium ion battery: same as step 2 of Example 1.
[0099] Comparative Example 1
[0100] 1. Preparation of coal tar pitch-based carbon material: Untreated coal tar pitch is carbonized at a high temperature of 1200°C under protective gas and kept at this temperature for 60 min to obtain a coal tar pitch-based carbon material.
[0101] 2. Preparation of sodium ion batteries:
[0102] (1) Grind the coal tar-based carbon material, acetylene black and binder PVDF obtained in step 1 in a mortar at a mass ratio of 8:1:1, then add 1-methyl-2-pyrrolidone solution until the powder is a black viscous slurry for later use;
[0103] (2) Using a 100 μm scraper, the slurry obtained in step (1) was evenly coated on a copper foil, and then the copper foil was dried at 60° C. for 6 h, and finally punched into a circular electrode sheet with a diameter of 12 mm, which was the negative electrode;
[0104] (3) The electrode sheet obtained in step (2) is used as the negative electrode, sodium metal is used as the positive electrode, glass fiber is used as the separator, 1 mol / L NaPF6 solution is used as the electrolyte, and the voltage range is (0.01-3) V to prepare a sodium ion battery.
[0105] Performance Testing
[0106] Figure 1 Flow chart of preparing boron-doped coal tar pitch-based carbon aerogel in Example 1.
[0107] Figure 2 This is a scanning electron microscope (SEM) image of the boron-doped coal tar pitch-based carbon aerogel prepared in Example 1. The results show that the boron-doped coal tar pitch-based carbon aerogel prepared in Example 1 is a porous material.
[0108] The electrochemical performance of the batteries prepared in Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 3 , Figure 3 The batteries prepared in Example 1 and Comparative Example 1 were -1 The first cycle charge-discharge curve under the voltage range of (0.01-3) V shows that at 0.1 A g -1 Under the voltage range of 0.01-3 V, the discharge capacity of the battery prepared in Example 1 is as high as 425 mAhg -1 , while the discharge capacity of the battery prepared in Comparative Example 1 is 245 mAh g -1 .
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing boron-doped coal tar pitch-based carbon aerogel, characterized in that: The preparation method comprises the following steps: (1) Dissolve PVA in deionized water, adjust the pH value to 8-10 with an alkaline solution, add coal tar and boric acid aqueous solution to obtain a coal tar-based hydrogel, wherein the mass ratio of coal tar to PVA is 1:(0.1-10); (2) The coal tar pitch-based hydrogel obtained in step (1) is freeze-dried and then subjected to high-temperature carbonization at a temperature of 1200-1500° C. to obtain the boron-doped coal tar pitch-based carbon aerogel.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the PVA in the deionized water is 1-10%; the alkaline solution is a NaOH solution or a KOH solution; and the concentration of the alkaline solution is (0.1-5) mol / L.
3. The preparation method according to claim 1, characterized in that: In step (1), the coal tar pitch is derived from lignite, bituminous coal or anthracite.
4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the boric acid aqueous solution is (1-5) mol / L.
5. The preparation method according to claim 1, characterized in that: The high temperature carbonization time is (60-120) min.
6. The preparation method according to claim 1, characterized in that: After the high-temperature carbonization, the aerogel is soaked in dilute hydrochloric acid, filtered and dried to obtain the boron-doped coal tar pitch-based carbon aerogel.
7. The preparation method according to claim 6, characterized in that: The concentration of the dilute hydrochloric acid is (1-4) mol / L.
8. Boron-doped coal tar pitch-based carbon aerogel prepared by the method according to any one of claims 1 to 7.
9. The use of the boron-doped coal pitch-based carbon aerogel according to claim 8, characterized in that: The boron-doped coal tar pitch-based carbon aerogel is used to prepare a sodium ion battery, and the negative electrode material of the sodium ion battery includes the boron-doped coal tar pitch-based carbon aerogel according to claim 8.
10. The use according to claim 9, characterized in that: The preparation method of the negative electrode material adopts the following steps: (1) The boron-doped coal tar pitch-based carbon aerogel, the conductive agent and the binder are uniformly mixed, and then a solvent is added and mixed to obtain a slurry; (2) The slurry obtained in step (1) is coated on a metal foil and vacuum dried to obtain the negative electrode material.
11. The use according to claim 10, characterized in that: In step (1), the mass ratio of the boron-doped coal tar pitch-based carbon aerogel, the conductive agent and the binder is (7-8): (0.5-1.5): (0.5-1.5).
12. The use according to claim 10, characterized in that: The conductive agent is carbon black, conductive graphite, carbon tube, graphene, Ketjen black, acetylene black or Super P; The binder is polyvinylidene fluoride, styrene-butadiene rubber latex or carboxymethyl cellulose.
13. The use according to claim 10, characterized in that: In step (1), the solvent is 1-methyl-2-pyrrolidone solution or water.
14. The use according to claim 10, characterized in that: In step (2), the vacuum drying temperature is (50-60)°C and the time is (6-24) h; the metal foil is copper foil or aluminum foil.
Citation Information
Patent Citations
Electrode material for all-vanadium redox flow battery constructed by boron-doped aerogel, preparation method and application thereof
CN111628188A
Preparation method of carbon aerogel, vanadium and manganese synergistically doped sodium ion battery positive electrode material
CN117525323A